2021
DOI: 10.1177/13694332211049991
|View full text |Cite
|
Sign up to set email alerts
|

Low-cycle fatigue life evaluation of buckling-restrained braces based on cumulative plastic deformation curves

Abstract: To quantitatively evaluate the low-cycle fatigue life of buckling-restrained braces (BRBs), an evaluation method for BRBs based on the combination of the CPD curves and CPD measurement meter (CMM) is established herein. The difference between two CPD curves (i.e., the CPD curves under constant strain amplitude loading history (C-CPD) and under random strain amplitude loading history (R-CPD)), and their selection criteria to evaluate the low-cycle fatigue life of BRBs are discussed. An example under the variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Due to their widespread use, modern codes for seismic retrofit (e.g., ASCE 41-17 [44]) and seismic design (e.g., AISC 341-16 [45], ASCE 7-16 [46]) have incorporated general guidelines for the design of BRB frames. However, BRBs are susceptible to low-cycle fatigue failure due to their limited cumulative ductility capacity [47][48][49][50][51][52], which limits their survivability in case of long-duration or repeated seismic sequences, possibly leaving a structure unprotected in the case of, e.g., main shock-aftershock sequences. Some authors of this paper have recently proposed a novel damper, named the PreStressed-Lead Damper (PS-LED), which dissipates seismic energy through the friction force triggered between a moving shaft and a lead core [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their widespread use, modern codes for seismic retrofit (e.g., ASCE 41-17 [44]) and seismic design (e.g., AISC 341-16 [45], ASCE 7-16 [46]) have incorporated general guidelines for the design of BRB frames. However, BRBs are susceptible to low-cycle fatigue failure due to their limited cumulative ductility capacity [47][48][49][50][51][52], which limits their survivability in case of long-duration or repeated seismic sequences, possibly leaving a structure unprotected in the case of, e.g., main shock-aftershock sequences. Some authors of this paper have recently proposed a novel damper, named the PreStressed-Lead Damper (PS-LED), which dissipates seismic energy through the friction force triggered between a moving shaft and a lead core [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the deformability of Q690 steel under monotonic loading and the fatigue life under LCF loading are lower than those of Q235 steel. Tong et al [11] evaluated the LCF life of buckling-restrained braces (BRBs), and they proposed an evaluation method for BRBs based on the combination of the cumulative plastic deformation curves. Yoon et al [12] studied the effect of multiple high-density pulsed electric currents on the LCF life of austenitic stainless steel.…”
Section: Introductionmentioning
confidence: 99%